STRATEGI PENGELOLAAN KELAS YANG EFEKTIF DISEKOLAH DASAR - Miftahul Jannah; Siti Teatresna Nivara; Desty Endrawati Subroto (CV. Denasya Smart Publisher, 2025)
This study aims to describe in depth the procedures for planning, implementing, and evaluating classroom management strategies, as well as the challenges and outcomes that arise from their implementation. The data collection process was carried out primarily through interviews with classroom teachers and direct observation of classroom management. After the data were collected, qualitative analysis of the existing instruments was carried out. The findings of this study indicate that the elementary school teachers surveyed were successful in planning, implementing, and evaluating their classroom management strategies well. They were also able to effectively address the challenges that arose. The implementation of these strategies had a positive impact on improving the quality of student learning, teacher professionalism, and the physical condition of the school environment. Effective classroom management is an important element in creating a comfortable, enjoyable, and productive learning environment. At the elementary school level, students are at various stages of development, so the approach used must be tailored to their needs. Effective teaching requires the implementation of various strategies that support each other. By building rapport with students, setting clear rules, and creating an engaging and supportive learning environment, teachers can help students reach their full potential. Therefore, it is essential for teachers to continue to develop themselves and adapt to changes in the classroom.